ISGT2011-India 2011
DOI: 10.1109/iset-india.2011.6145377
|View full text |Cite
|
Sign up to set email alerts
|

A review on multi-agent systems in microgrid applications

Abstract: The application of Multi-Agent Systems (MAS) in electrical power systems are becoming popular due to their inherent benefits such as increased autonomy, reactivity, proactivity and social ability. This paper reviews current research on the application of multi-agent systems in microgrid schemes. The paper is mainly focused on recent developments of multi-agent systems in different aspects of microgrids such as control, market modeling, optimization and power restoration. The future directions of multi-agent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 42 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…In both these studies the multi-agent control system was able to learn occupancy trends and optimize building energy demand. MAS have also gained popularity in other fields of energy as well, a review on MAS applied on microgrid systems can be found in (Kulasekera et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In both these studies the multi-agent control system was able to learn occupancy trends and optimize building energy demand. MAS have also gained popularity in other fields of energy as well, a review on MAS applied on microgrid systems can be found in (Kulasekera et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of MAS has been wide applied to various problems in microgrid research, such as power management [12], distributed optimization [13], active power and reactive power control [14]. Existing MAS based applications in power systems are usually rule-based and lacked rigorous stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-agent system (MAS) is one of the most popular distributed control approaches in literature [11]- [14]. The concept of MAS has been wide applied to various problems in microgrid research, such as power management [12], distributed optimization [13], active power and reactive power control [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers such as [23][24][25][26][27][28][29][30] have proposed frameworks and guidelines for the design, modeling and development of MAS with a correct view on how they should act, interact, socialize and pursue the goal, which is the power management solution of their power system. It is not intended to classify solutions in the microgrids as in [31][32][33] and for MAS as presented at [34][35][36].…”
Section: Introductionmentioning
confidence: 99%